Anthropogenic heat due to energy consumption contributes to cooler and wetter summers in Southwest China - Zhang, Mengyi; Zhao, Jingchuan; Chen, Bing; Zheng, Yuhao; Lu, Mingwei; Wu, Xue; Yang, Huiyi; Liu, Xiaohong; Wu, Chenglai; Zhang, Meigen; Zhao, Xiaoqing; Jinlin, Zha; et al. (Frontiers in Earth Science, 2023)
Anthropogenic heat release is the release of heat generated by anthropogenic energy consumption. The regional mean Anthropogenic heat release flux in Southwest China grew quickly from 0.06 Wm-2 in 1992 to a peak of 0.37 Wm-2 in 2019. This study examines the climatic effects and feedbacks of Anthropogenic heat release due to energy consumption in Southwest China during the boreal summer using simulations from the Community Earth System Model. The modeling results show that Anthropogenic heat release impacts on the lower-troposphere stability and affects large-scale atmospheric circulation in Southwest China, which transports more water vapor and consequently increases the humidity and low cloud cover in Southwest China. This effect impacts the energy balance at the surface by reducing the amount of incoming shortwave radiation that reaches the ground. Anthropogenic heat release decreases the average 2-m air temperature in Southwest China by 0.10 ± 0.01 K (1σ uncertainty) and also decreases the minimum and maximum air temperatures in Southwest China as well. Anthropogenic heat release contributes to cooler and wetter summers in Southwest China. The results show that Anthropogenic heat release is a non-negligible factor that impacts the climate of Southwest China. This study improves our understanding of the climate change resulting from human activities in Southwest China.